Tourism Development Policy based on Sustainable Tourism Development in Improving Community Welfare Mahakam Regency - Mujarni Baraq; Sri Kamariyah; Ika Devy Pramudiana; Zainal Fatah (Studi Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to describe and analyze: Tourism development policies in improving community welfare are reviewed from the approach of sustainable tourism development in Mahakam Regency. Factors that support and hinder tourism policies in improving people's welfare. Tourism development policy model as a recommendation to support sustainable tourism development. This research is a qualitative research, with data collection techniques using interviews, observations, and documentation. Data analysis techniques Interactive data analysis. The results of the study show that sustainable tourism development in Mahakam Regency is a policy in development with economic, socio-cultural, and environmental dimensions based on justice not only for the current generation but also for future generations. The policy must have two objectives, namely to maximize the contribution of tourism resources that have been proven to be able to provide added value economically. The policy requires tourism business actors to prioritize and preserve cultural uniqueness as well as optimize the role of local communities. Policies on the environmental aspect can be preventive and repressive by involving all stakeholders from tourism Supporting factors for sustainable tourism development in Mahakam Regency include natural conditions that are still maintained as tourist attractions and support for the community around tourist destinations. Factors inhibiting sustainable tourism development in Mahakam Regency are limited infrastructure, lack of promotion, and unsupportive environmental conditions.